Disclosure of Non-Financial Information: Theoretical Readings and Analysis - الفضلي د. خالد زيدان; الحصادي د. سامي سالم (Dirasat in Economics and Business, 2022)
The study aimed to provide the-oretical readings and analyzes ab-out the disclosure of non-financial information, based on the inductive approach, through an objective ext-rapolation of previous relevant stu-dies. The importance of disclosing non-financial information helps and enables stakeholders to make their decisions positively, as a result of its inclusion of environmental, soc-ial, governance, strategic and risk disclosures, and that the stages that non-financial disclosure went thro-ugh were divided into four periods, where the form of disclosure was in the form of A unified report that contains financeial and non-finan-cial information at the same time, and this is what is known as int-egrated business reports. As for the type of information included in this report, it is information on the environmental, social, governance, strategy, and risks dimensions. The relative importance of in-formation disclosure faces major challenges associated with the lack of stand-ards governing its importance. As a result of the difference and dive-rsity of information, as well as the different decisions of stakeholders, and in general, the benefit of this information is the basic criterion that governs the relative import-ance. While it was found that the theories supporting non-financial disclosure do not fundamentally di-ffer among themselves, they all emphasize the expansion of disc-losure processes to reduce info-rmation asymmetry. The international initiatives to disclose information included; The Global Reporting Initiative, the International Reporting Council In-itiative, the American Initiatives, and the Libyan Initiatives to Dev-elop Disclosure of Non-Financial Information, all of which had a ma-jor role in developing non-financial disclosure.